Band gaps in the relaxed linear micromorphic continuum. Issue 9 (30th June 2014) - Madeo, A.; Neff, P.; Ghiba, I.‐D.; Placidi, L.; Rosi, G.
<x xml:space="preserve">Abstract</x> The authors show that the relaxed linear micromorphic model recently proposed by the authors can be suitably used to describe the presence of band‐gaps in metamaterials with microstructures in which strong contrasts of the mechanical properties are present (e.g. phononic crystals and lattice structures). This relaxed micromorphic model only has 6 constitutive parameters instead of 18 parameters needed in Mindlin‐ and Eringen‐type classical micromorphic models.